Finance Performance of Manufacturing Companies Affected by Corporate Social Responsibility Disclosure - M Meiryani; Edbert Stefan Houten; Ahmad Syamil (Jurnal ASET (Akuntansi Riset), 2024)
Corporate Social Responsibility (CSR) refers to an organization's endeavors to enhance the well-being of a local or global community by means of diverse initiatives undertaken by the organization. It is important to reveal the activities conducted into a report, both in the annual report and the sustainability report, in order to maintain the company's positive reputation among the general public who might not be able to feel the effects of the activities firsthand. The purpose of this study was to determine whether CSR disclosure has an impact on LQ45 companies' financial performance. The Indonesia Stock Exchange (IDX) website or the company's official website are the sources of the annual reports or sustainability reports that are used in this study. Content analysis techniques are used to the data collection procedure. In order to process the data, the significance of the influence between the bound and free variables is ascertained using a straightforward regression analysis. The results of this study show that there is an influence between CSR disclosures on the financial performance of LQ45 companies as measured by Return on Asset (ROA), Return on Sales (ROS), and Gross Profit Margin (GPM). Based on authors knowledge this is first study conduct CSRI on return on asset, return of sales and gross profit margin on LQ45 manufacturing companies.